Incorporation of lipid nanosystems containing omega-3 fatty acids and resveratrol in textile substrates for wound healing and anti-inflammatory applications - Silva, Juliana (2020)
In the present work, lipid nanosystems containing omega-3 fatty acid (nanostructured lipid carriers, NLCs) or omega-3 fatty acid and resveratrol (liposomes) were developed to improve cotton textile substrates as dressings with anti-infammatory properties for wound healing applications. Lipid nanosystems were incorporated into woven, non-woven and knitted cotton substrates by exhaustion and impregnation. Based on physical–chemical characterization of the textile substrates, the textile structure and type of lipid nanosystems dictated the adsorption efciency. In the case of NLCs, the woven substrate functionalized by exhaustion had a higher omega-3 release being the most promising for wound dressing application. Whereas for liposomes, the most adequate textile was the cationized knitted fabric functionalized by impregnation, that showed a more prolonged release profle of resveratrol.